Koperasi Desa Merah Putih sebagai Strategi Kebangkitan Ekonomi Lokal Berbasis Partisipasi Masyarakat : Analisis Modal Sosial Pierre Bourdieu - Hasan Afandi, Ahmad; Fachruddin, Imam; Heru Widodo, Mochammad (MAJAPAHIT POLICY, 2025)
The Merah Putih Village Cooperative is a strategic instrument in efforts to revive the local economy based on community participation. This study aims to analyze the role of village cooperatives in strengthening the local economy using Pierre Bourdieu's social capital theory framework, specifically in the context of social relations, trust networks, and collective practices of village communities. This study employed a descriptive qualitative approach through a literature review of national and international scientific journals, recent academic books, and policy documents and laws governing cooperatives and village development in Indonesia. The results show that active community participation in the Merah Putih Village Cooperative contributes significantly to the formation and strengthening of social capital, which serves as the foundation for the sustainability of cooperative institutions. This social capital enables village cooperatives to function not only as economic entities but also as production spaces for social solidarity and economic democratization at the local level. In the context of the dominance of oligarchic economic structures and the expansion of modern retail in rural areas, village cooperatives emerge as an economic alternative based on collective ownership that can strengthen the independence and economic sovereignty of village communities. Thus, the Merah Putih Village Cooperative has strategic potential as an instrument for inclusive, equitable, and sustainable local economic development.